Strategi Guru Tahfidz Dalam Meningkatkan Hafalan dan Menjaga Hafalan Santri di Rumah Tahfidz Barokalloh Kalipare - aziza, ilma fahmi; Musaddat, Irfan; arifa aini, mifta (AL-WIJDÃN Journal of Islamic Education Studies, 2021)
This study aims to determine the strategy of Tahfidz teachers at Tahfidz Barokalloh Kalipare House to: (1). improve students' memorization of the Qur'an. (2). maintain the memorization of the students of the Qur'an. (3). inhibiting and supporting factors. The research method used is qualitative research with a case study qualitative research type obtained through three techniques: observation, interviews, and documentation. Based on the results of the research, it can be said that the strategy consists of several actions, namely: a) Providing motivation, b) Giving daily memorization tasks and targets, c) Guiding students always to be murojaah, d) Graduation for those who meet the memorization target. e) as the initiator, provider, inspiration, mentor, and motivator